'Sçavoir bien badiner est un grand avantage': Monkey Business in the Labyrinth of Versailles. Issue 2 (3rd July 2019) - Rife Bastin, Kathryn
Abstract : The Labyrinth of Versailles was a splendid horticultural space in early modern France frequented by courtiers and very likely by Louis XIV's son the dauphin. In this article, the author argues that the Labyrinth stood as a vital locus of etiquette formation for the court, and more widely, the surrounding Parisian villages and early modern Europe at large. Fouquet's usurpation of kingly authority comes into play, as well as political allegory, that tie together to show the crucial nature of the Labyrinth as an architectural space that ultimately influences comportment of the era. The author examines texts by Charles Perrault, Isaac de Benserade, and engravings by Sébastien Le Clerc. She considers two of the most important fountains within the verdant passageways, those of the monkey king and the monkey judge, which showcase the critical nature of imitation for acceptable comportment of the period.